Comparative life cycle assessment of ceramic brick, concrete brick and cast-in-place reinforced concrete exterior walls. (20th November 2016) - Maia de Souza, Danielle; Lafontaine, Mia; Charron-Doucet, François; Chappert, Benoit; Kicak, Karine; Duarte, Fernanda; Lima, Luis
Abstract: The construction sector has a meaningful contribution to the global scarcity of natural resources, as well as to impacts on the natural environment. Most life cycle assessments have focused on impacts associated with the energy efficiency of buildings, in particular during the operational phase. However, the construction phase of buildings accounts for a significant share of a building's embodied energy and is responsible for impacts related to resource depletion. With the aim to contribute to more all-embracing assessments in the construction sector, this study aims to compare three different wall types commonly used in Brazil, according to their environmental performances: ceramic brick, concrete brick and cast-in-place reinforced concrete exterior walls. The results were analyzed with the software SimaPro 7.3 and with the life cycle impact assessment method IMPACT 2002+ (version Q2.2). Ceramic brick walls have less impact than the concrete brick and the cast-in-place reinforced concrete exterior walls on three different endpoint indicators (Climate Change, Resource Depletion and Water Withdrawal). The results were not significant regarding impacts on Human Health and Ecosystem Quality. Different sensitivity analyses were carried out in order to test the final results, as well as uncertainty analysis, related to the variability of inventory data and the characterization of the life cycle inventory results into midpoints and/or endpoints. Highlights: We compared the environmental impacts of three wall types commonly built in Brazil. Differences in impacts mainly result from the use of distinct natural resources and processes. We run different sensitivity analyses to test the final results. The concrete manufacturing process has a great impact on Climate Change and Resource Depletion. The environmental performance of ceramic bricks is improved by filtering fine particulate matter.